ALCOHOL CONSUMPTION AND MICROVASCULAR DYSFUNCTION: A J-SHAPED ASSOCIATION– THE MAASTRICHT STUDY. (June 2022) - Heide, Frank van der; Eussen, Simone; Houben, Alfons; Henry, Ronald; Kroon, Abraham; Kallen, Carla van der; Dagnelie, Pieter; Dongen, Martien Van; Berendschot, Tos; Schouten, Jan; Webers, Carroll; Schram, Miranda; et al.
Abstract : Objective: Alcohol consumption may be a determinant of microvascular dysfunction (MVD), an important contributor to major clinical disease such as stroke, dementia, depression, retinopathy, and chronic kidney disease. Main objectives were 1) to study whether alcohol consumption was associated with MVD as assessed in the brain, retina, skin, kidney and in the blood; and 2) to investigate whether associations differed by history of cardiovascular disease or sex. Design and method: We used cross-sectional data from The Maastricht Study (N = 3, 120 participants, 50.9% men, mean age 60 years, 16.8% with a history of cardiovascular disease, and 27.5% with type 2 diabetes [the latter oversampled by design]). We used regression analyses with adjustment for potential confounders to study the association between total alcohol, consumption (moderate versus light) and MVD, where all measures of MVD were combined into a total MVD composite score (expressed in standard deviation "standardized beta''). We tested for interaction by history of cardiovascular disease and sex. Results: The association between total alcohol consumption and MVD was non-linear, i.e. J-shaped. Moderate versus light total alcohol consumption was significantly associated with less MVD, after adjustment for potential factors (moderate versus light total alcohol consumption, standardized beta [95% confidence interval], -0.10 [-0.19; -0.01]). History of cardiovascular disease (Pinteraction < 0.001) and sex (Pinteraction = 0.03) modified the associations. In stratified analyses the mathematical minimum was at higher levels of alcohol consumption for individuals with, versus without, a history of cardiovascular disease and for men versus women. In addition, moderate versus light alcohol consumption was considerably more strongly associated with less MVD in individuals with, versus without a history of cardiovascular disease; however, the strength of this association did not materially differ between women and men. Conclusions: The present population-based study found a J-shaped association between alcohol consumption and MVD, where the exact shape of the association differed by history of cardiovascular disease and sex. Therefore, alcohol consumption may be a determinant of MVD. Hence, although increasing alcohol consumption cannot be recommended as a policy, this study suggests that prevention of MVD may be possible through dietary interventions.